Smoke control in tunnel with a transverse ventilation system: An experimental study. (January 2020) - Chaabat, F.; Salizzoni, P.; Creyssels, M.; Mos, A.; Wingrave, J.; Correia, H.; Marro, M.
Abstract: We carried out a series of experiments in a small-scale tunnel to study the confinement of smoke flow between two exhaust vents located on either side of a buoyant source placed at ground level within a ventilated tunnel. The objective of our study is to quantify the influence of the shape and the position (with respect to the tunnel axis) of the dampers, including the specific case of full-width dampers, on the performance of the transverse ventilation system. To that purpose, we investigated the extent of the backflow length downstream of the dampers, the "confinement velocity" (suppressing the back-layering flow downwind of the vents) and the stability of the smoke stratification. The results show that the best performances are achieved when the width of the dampers is the same as the tunnel width: this minimises the extent of the back-layering flow (for given extraction flow rates) and ensures the stability of the smoke stratification. The worst conditions are observed with square-shaped dampers located on the side of the ceiling, this configuration disturbs the stratification of the smoke layer before the confinement conditions are reached. Subsequently, we evaluated the effect of solid barriers -placed on the tunnel ceiling downstream of same three dampers typologies-on the propagation of the smoke. The results show that these barriers improve significantly the efficiency of system with square-shaped dampers located on the side of the ceiling: they reduce the confinement velocity and enhance the stability of the smoke stratification. Highlights: We study the control of smoke propagation in a tunnel with transverse ventilation. Form and position of exhaust vents have a great influence on smoke propagation. Transverse rectangular dampers perform better than square dampers. The efficiency of square vents can be improved by placing mobile barriers.